Detection of Extended Spectrum β-lactamase (ESBL) And Carbapenemase Encoding Escherichia coli isolates from hospital effluent wastewater and hospital adjacent community tap water in Dhaka metropolitan city - Tishan, Salman Habib; Haque, Md Najmul; Hasan, Arnab (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology and Bachelor of Science in Microbiology, 2023.